Efficacy and safety of patient‐directed titration of once‐daily pre‐dinner premixed biphasic insulin aspart 70/30 injection in Japanese type 2 diabetic patients with oral antidiabetic drug failure: STEP‐AKITA study - Narita, Takuma (Blackwell Publishing Ltd, 2011)
Aims/Introduction:  To clarify clinical characteristics related to optimal glycemic control achieved after adding once‐daily pre‐dinner biphasic insulin aspart 70/30 (BIAsp 30) in Japanese type 2 diabetic (T2D) patients with oral antidiabetic drug (OAD) failure. Materials and Methods:  Under this regimen, we evaluated changes in HbA(1c) levels and daily self‐monitoring blood glucose (BG) profiles, as well as the incidences of hypoglycemia and retinopathy progression. The patients adjusted BIAsp 30 dosages themselves every 3–4 days according to a pre‐determined algorithm to achieve fasting BG levels of 101–120 mg/dL. HbA(1c) levels were expressed as Japan Diabetes Society values. Results:  Of 29 enrolled patients, 22 (HbA(1c) levels, 8.5 ± 1.5% [mean ± SD]) and 20 patients completed the 16‐ and 24‐week follow‐up, respectively. At 16 weeks 68.2 and 45.5%, and at 24 weeks 80.0 and 35% of patients had achieved HbA(1c) levels of <7.0 and <6.5%, respectively. The patients who had achieved optimal glycemic control, including daytime postprandial BG profiles after treatment, had lower post‐breakfast BG excursions at baseline, shorter diabetes durations and younger age. No severe hypoglycemic episodes were recorded. Progression of retinopathy was observed in 3 of the 29 enrolled patients. Conclusions:  Lower post‐breakfast BG excursions, shorter diabetes duration and younger age in Japanese T2D patients with OAD failure might warrant optimal glycemic control with safety after adding once‐daily pre‐dinner BIAsp 30 initiating regimen. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2010.00062.x, 2010)